2011
DOI: 10.1380/ejssnt.2011.215
|View full text |Cite
|
Sign up to set email alerts
|

Molar Concentration Dependence of Sucrose Solution in Carbon Nanotube Synthesis by Liquid-Phase Arc Discharge

Abstract: We synthesized carbon nanotubes (CNTs) from sucrose solution, used as a carbon source, by the liquid-phase arc discharge method, which generates electric sparks between metal electrodes. The quality of the CNTs depends on the molar concentration of sucrose solution because the discharge characteristics vary with its viscosity. When a lower density solution, 0.5 mol/L in this study, was used, the G/D ratio of the generated CNTs was the highest. This result implies that discharge characteristics dependent on sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We previously demonstrated the production of shorter and high-crystallinity CNTs using a sucrose solution as a carbon supplier [11]; however, electron microscopy revealed the formation of only a few nanotubes in the specimen, suggesting that the sample contained a high proportion of metal particles. Moreover, we recently found that discharge characteristics dependent on sucrose concentration play an important role in CNT synthesis by liquid-phase arc discharge [12]. This experiment determined that the number of electric sparks decreases with an increasing molar concentration of the sucrose solution.…”
Section: Introductionmentioning
confidence: 92%
“…We previously demonstrated the production of shorter and high-crystallinity CNTs using a sucrose solution as a carbon supplier [11]; however, electron microscopy revealed the formation of only a few nanotubes in the specimen, suggesting that the sample contained a high proportion of metal particles. Moreover, we recently found that discharge characteristics dependent on sucrose concentration play an important role in CNT synthesis by liquid-phase arc discharge [12]. This experiment determined that the number of electric sparks decreases with an increasing molar concentration of the sucrose solution.…”
Section: Introductionmentioning
confidence: 92%
“…Different methods for the formation of CNTs, such as chemical vapor deposition (CVD), electric-arc discharge, [6] laser ablation, [7] the catalytic decomposition of hydrocarbons, [8] electrolysis, [9] and low-temperature solid pyrolysis, [10] have been reported. For some applications, it is necessary to achieve ordered CNT architectures: The use of CNTs in FETs or in thin-film transistors (TFTs) requires the control of CNT growth at predefined locations.…”
Section: Introductionmentioning
confidence: 99%
“…To synthesize nano-carbon materials including CNTs, we have performed an arc discharge method in water [14,15], in foam [16][17][18][19], or in sucrose solution [20,21]. The formation of M@CNTs by using metal, which is incorporated into CNTs, as the cathode was also reported [14].…”
Section: Introductionmentioning
confidence: 99%